Particleboard manufactured from six species of Amazon tropical timbers - Iwakiri, Setsuo; Trianoski, Rosilani; do Nascimento, Claudete Catanhede; Francisco Juizo, Claudio Gumane; Lengowski, Elaine Cristina; Katalyne Bilcati, Géssica; Gonçalves, Thais (Instituto de Ecología, A.C., 2018)
This research aimed to evaluate the quality of particleboard produced with six Amazonian tropical woods: Byrsonima crispa, Eschweilera coriacea, Eschweilera odora, Manilkara amazonica, Pouteria guianensis and Swartzia recurva. Experimental panels were produced with nominal density of 0,75 g/cm³, using the urea-formaldehyde resin in a proportion of 8% solids based on dry weight of the particles. The panels were pressed with a specific pressure of 4,0 MPa, temperature of 160 °C and pressing time of eight minutes. The panels were evaluated based on the following properties: compression ratio, water absorption and thickness swelling for 2 hours and 24 hours, modulus of elasticity and modulus of rupture, tension perpendicular, screws pullout resistance on the surface and top. Low compression ratio of panels produced with tropical wood species did not affect significantly the results of their physical and mechanical properties. Comparative evaluation of the results obtained with the requirements of EN 312 (2003) and reference species - Pinus taeda, showed that Byrsonima crispa, Eschweilera coriacea, Eschweilera odora and Pouteria guianensis have great potential for the production of particleboard.